Determinants of Costs-Efficiency for Commercial Banks Operating in Algeria Econometric Study during the Period 2010 – 2016 - Mohammed, FOUDOU; Belkacem, MIMOUNI; Achouak, BENKADDOUR (Milev Journal of Research and Studies, 2020)
This study aims to reveal the cost-efficiency determinants of banks expressed at a profit margin rate for all commercial banks operating in Algeria during the period (2010 - 2016) using the Panel models. Among the most important results reached are the presence of statistical significance between the profit margin rate and both of the cost of financing the bank, the cost of fixed capital for the bank and the size of the bank, which is consistent with the logic of economic theory, while creating insignificant statistical relationship between the profit margin rate and the cost of operating the bank, which is not Corresponds to the logic of economic theory. This result was explained by the lack of optimal utilization of operating resources and insufficient response to the qualification requirements imposed by the information revolution, which affects the work of banks. It was also reached that the structure of the chosen cost ratios (the ratio of the bank’s financing cost, the bank’s operating cost ratio, the fixed capital cost ratio and the size of the bank) explain 85.6% of the cost-efficiency changes of banks operating in Algeria represented by the profit margin index